Why do we teach the mathematics that we do? The case of Lithuanian school mathematics - Norvaiša, Rimas (Lietuvos matematikos rinkinys, 2019)
Due to the changes of education system the school mathematics in Lithua-nia have acquired the elements of commercial-administrative mathematics of ancient times. Among other consequences the opportunities of school children to achieve the standards of mathematical reasoning are limited.
Keywords: learning paradigm; teaching paradigm; education reforms; school mathematics; political economy of math education